Different Percentages of Gonad Maturity on The Fertility and Haching Rate in Artificial Breeding of Abalone (Haliotis asinina) - Suminto Suminto (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2010)
Abalone is one of the marine mollusk that has high economic value. Mass abalone cultivation requires the mature gonads broodstock to produce seeds, but the maturity of the gonads of male and female often can not be simultaneously. Artificial insemination using a solution of ammonia is one solution to produce abalone seed in the hatchery. Ammonia solution can increase motility, fertilization rate of eggs and abalone seed production, so the provision of seeds for cultivation of abalone is independent from nature. The research of artificial insemination was carried out at various levels of gonadal maturation dams abalone (H. asinina) to determine the percentage of fertility and hatching rate of eggs from each Gonad Maturity Level. In stadia gonadal recovery, no fertilization occurs, whereas in the gonads maturing stadia had fertilization and hatching rate 24.33 ± 2.08% and 22.12 ± 2.18%, respectively at ripe stadia, gonads had been fertilization and hatching rate were 94.67% ± 1.53% and 82.82% ± 3.58%, wasn’t recorded in the stadia spent fertilization did not occur because the eggs were released in culture media. Gonad Maturity Level, thus can be used in artificial insemination was the ripe gonadal stadia, which had the highest percentage of both levels of fertilization and hatching rate with a diameter ranging from 189.6-252.8 μm.   Key Words : Abalone (H. asinine); Artificial breeding; Gonad Maturity Level; Hatching Rate